An analysis of three selected stories from Orbit 21 using Patrick Parrinder's genre criticism - Buenafe, Paul R. (Animo Repository, 1996)
Science fiction is a developing genre in Philippine literature. As a genre the particular view science fiction and its authors has scarcely been given attention to. The aim of this paper is to present the particular view of one author through Patrick Barrinder's genre criticism of science fiction. The criticism gives a comprehensive view of the genre over since its conception and provides a comprehensive understanding of science fiction.